Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 95837 by mathmax by abdo last updated on 28/May/20

let p(x)=(1+ix+x^2 )^n −(1−ix +x^2 )^n   1) determine roots of p(x)  2) find p(x) at form Σ a_i  x^i   3)ddtermne p(x) at form arctan  4) factorize p(x) inside C[x]  5) calculate ∫_0 ^1  p(x)dxand ∫_1 ^∞  (dx/(p(x)))

letp(x)=(1+ix+x2)n(1ix+x2)n1)determinerootsofp(x)2)findp(x)atformΣaixi3)ddtermnep(x)atformarctan4)factorizep(x)insideC[x]5)calculate01p(x)dxand1dxp(x)

Answered by mathmax by abdo last updated on 02/Jun/20

1) p(x)=0⇔(1+ix+x^2 )^n =(1−ix +x^2 )^n  ⇒(((1+ix+x^2 )/(1−ix+x^2 )))^n  =1 let  z =((1+ix +x^2 )/(1−ix +x^2 )) ⇒1+ix+x^2  =z−izx+zx^2  ⇒x^2  +ix+1−zx^2 +izx−z =0 ⇒  (1−z)x^2  +i(z+1)x +1−z =0  Δ =−(z+1)^2 −4(1−z)^2   ⇒x_1 =((−i(z+1)+i(√((z+1)^2  +4(z−1)^2 )))/(2(1−z)))  x_2 =((−i(z+1)−i(√((z+1)^2  +4(z−1)^2 )))/(2(1−z)))  z^n  =1 ⇒z^n  =e^(i2kπ)  ⇒z_k =e^((i2kπ)/n)   with k∈[[0,n−1]] ⇒the roots are  x_(1k) =((−i(z_k +1)+i(√((z_k +1)^2  +4(z_k −1)^2 )))/(2(1−z_k )))  or  x_(2k) =((−i(z_k +1)−i(√((z_k +1)^2  +4(z_k −1)^2 )))/(2(1−z_k )))

1)p(x)=0(1+ix+x2)n=(1ix+x2)n(1+ix+x21ix+x2)n=1letz=1+ix+x21ix+x21+ix+x2=zizx+zx2x2+ix+1zx2+izxz=0(1z)x2+i(z+1)x+1z=0Δ=(z+1)24(1z)2x1=i(z+1)+i(z+1)2+4(z1)22(1z)x2=i(z+1)i(z+1)2+4(z1)22(1z)zn=1zn=ei2kπzk=ei2kπnwithk[[0,n1]]therootsarex1k=i(zk+1)+i(zk+1)2+4(zk1)22(1zk)orx2k=i(zk+1)i(zk+1)2+4(zk1)22(1zk)

Answered by mathmax by abdo last updated on 02/Jun/20

2) we have p(x) =(1+x^2  +ix)^n −(1+x^2 −ix)^n   =Σ_(k=0) ^n  C_n ^k (ix)^k  (1+x^2 )^(n−k)  −Σ_(k=0) ^n  C_n ^k (−ix)^k (1+x^2 )^(n−k)   =Σ_(k=0) ^n  C_n ^k (1+x^2 )^(n−k) { i^k −(−i)^k }x^k   =Σ_(p=0) ^([((n−1)/2)])  C_n ^(2p+1)  (1+x^2 )^(n−2p−1)  (2i)(−1)^p  x^(2p+1)   =2iΣ_(p=0) ^([((n−1)/2)])  (−1)^p  C_n ^(2p+1)  x^(2p+1) (Σ_(k=0) ^(n−2p−1)  C_(n−2p−1) ^k  x^(2k) )  =2i Σ_(p=0) ^([((n−1)/2)])  (−1)^p  C_n ^(2p+1) (Σ_(k=0) ^(n−2p−1)  C_(n−2p−1) ^k  x^(2k+2p+1) )

2)wehavep(x)=(1+x2+ix)n(1+x2ix)n=k=0nCnk(ix)k(1+x2)nkk=0nCnk(ix)k(1+x2)nk=k=0nCnk(1+x2)nk{ik(i)k}xk=p=0[n12]Cn2p+1(1+x2)n2p1(2i)(1)px2p+1=2ip=0[n12](1)pCn2p+1x2p+1(k=0n2p1Cn2p1kx2k)=2ip=0[n12](1)pCn2p+1(k=0n2p1Cn2p1kx2k+2p+1)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com